2010
DOI: 10.3346/jkms.2010.25.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Follow-up Results of External Beam Radiotherapy as Primary Treatment for Retinoblastoma

Abstract: The authors reviewed their experiences of external beam radiotherapy (EBR) as an initial treatment in retinoblastoma patients to determine its long-term effect on subsequent tumor control and complications. A total of 32 eyes in 25 patients that underwent EBR for retinoblastoma were reviewed retrospectively. The patients consisted of 21 boys and 4 girls of median age at treatment of 7.1 months. Radiation doses ranged from 35 to 59.4 Gy. The 10-yr ocular and patient survivals were 75.4% and 92.3%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Craniofacial deformities are reported after radiotherapy for head and neck tumors (7274) including retinoblastoma (68) and rhabdomyosarcoma (69, 7580). In a recent study, all of 25 retinoblastoma survivors treated with 35–54.9 Gy and followed for 5 to 21 years presented with midfacial hypoplasia (68).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Craniofacial deformities are reported after radiotherapy for head and neck tumors (7274) including retinoblastoma (68) and rhabdomyosarcoma (69, 7580). In a recent study, all of 25 retinoblastoma survivors treated with 35–54.9 Gy and followed for 5 to 21 years presented with midfacial hypoplasia (68).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, all of 25 retinoblastoma survivors treated with 35–54.9 Gy and followed for 5 to 21 years presented with midfacial hypoplasia (68). Another study reported facial deformity in 73% of survivors of head and neck rhabdomyosarcoma exposed to 41.4–65.0 Gy and followed for a median of 20 years (75).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate visual impairment is seen in 10-23% of eyes, whereas poor or no useful vision was in 20-41.7% of non-enucleated eyes. The best visual outcomes are noted in patients with early stages that spared the optic disc, macula, and fovea, suggesting that the location of tumors has an impact of visual outcome even after PRT [35][36][37][38].…”
Section: External Beam Radiation Therapy (Ebrt)mentioning
confidence: 99%
“…Cataracts were the most common long-term complication in eyes treated with EBRT. Other ocular complications noted are radiation retinopathy, glaucoma, neovascularization, vitreous hemorrhage, retinal detachment, strabismus, and less common toxicities [35][36][37][38].…”
Section: External Beam Radiation Therapy (Ebrt)mentioning
confidence: 99%